Drawing on the project initiators’ perspectives to evaluate TURF implementation in the Kepulauan Seribu Marine National Park: an online Q methodology study - Furqan, Rifki; Schlüter, Achim (Frontiers in Marine Science, 2023)
Territorial User Rights for Fisheries (TURF) are established to grant privileged rights exclusively to local fishing communities to manage their stock within a bounded fishing ground. Theoretically, they will improve their sense of ownership which will eventually lead to stewardship and responsibility. In Indonesia, contemporary TURF has been introduced to meet such social outcomes and address the overfishing problems caused by open-access systems. The primary objective of this study was to determine how different project initiators perceive the system’s performance of TURF in Kepulauan Seribu Marine National Park. This study used an online Q methodology to determine what key actors thought of similarities and differences in TURF implementation by developing a concourse based on the original TURF project success elements. The results show that there are two different perspectives on what the essential aspects of TURF succeed in Kepulauan Seribu. The first opinion group appreciated the technical design of TURF, particularly the exclusion mechanism and boundary, which are crucial. A second opinion group argues that the clarity of rights, roles, and responsibilities is fundamental. Both opinion groups agreed that consistent law enforcement is the key to a successful TURF implementation. This study evaluated key stakeholders’ perspectives on co-management programs to identify points of consensus and disagreement that could ultimately help ensure the long-term success of TURF and similar co-management programs.